Challenges of ’Dual Distribution’ - Dhotre, Meenal (Indian Journal of Marketing, 2006)
In the past, firms used to sell to a single market through a single channel. Gone are the days of one exclusive dealership per city. The ideal of this century business is a use of multiple channels, master of bricks, clicks and flips-with physical stores, online shopping and catalogues integrated into a seamless environment. This commercial paragon is bracing for a future that will include even more contact opportunities, such as interactive kiosks, personal digital assistants, wireless phones and yet-to-be-invented technologies.